Clusiaceae s.l. (Calophyllaceae, Clusiaceae s.s. and Hypericaceae) in the Viruá National Park, Roraima, Brazil - Cabral, Fernanda Nunes; Bittrich, Volker; Hopkins, Michael John Gilbert (Phytotaxa, 2017)
We report a floristic survey of the species of Clusiaceae s.l. (Calophyllaceae, Clusiaceae s.s., and Hypericaceae) in the Viruá National Park (Roraima, Brazil). The fieldwork was conducted between 2009 and 2015 and covered the different vegetation types found in the park. Calophyllaceae is represented by two genera and three species, Clusiaceae s.s. by five genera and 12 species, and Hypericaceae by one genus and five species. Three species are new records for the state of Roraima. We present an identification key, updated taxonomic descriptions, and photographic illustrations for each species. Two lectotypifications are proposed for Clusia. A new combination in Garcinia is also proposed.